Continuing Connection: Roles of Makassan Artists in Retelling a Shared History between Trepangers and Indigenous Australians - Lily Yulianti Farid; Muhammad Arief Al Fikri (LIPI Press, 2021)
The historical relationships between Makassans and Aboriginal people that took place as early as the 17th century until the early 20th century through the trepang industry in the northern coast, North Australia, is still unknown to many people in Makassar, South Sulawesi. There are various factors involved in the lack of information about the shared history, including the absence of the story of trepangers as part of Indonesian maritime heritage history in school textbooks and the insufficient materials and narratives on this topic in provincial and city museums. This paper examines the potential roles of Makassan artists and cultural activists to tell the story after engaging with ancient trepang industry-related cultural and art projects. It also investigates their changed perceptions about Australia and Indonesia both culturally and historically after their participation in art and cultural projects.